Aid and development effectiveness : towards human rights, social justice and democracy : Reality of Aid 2010 report - Wilks, Alex (IBON Books Quezon CityPH, 2010)
Demonstrates that implementation of aid effectiveness reforms for management and delivery unde the Paris Declaration and the Accra Agenda for Action are far from optimal at country level. Finds that severe fragmentation of cooperation efforts and the dichotomies of North-South and South-South cooperation perpetuate ineffectiveness and anti-development power relationships.